A Syrian Child with Intussusception Caused by a Diffuse Large B-Cell Lymphoma - Rahaf Toutounji; Ahmad Ghazal; Aghyad kudra Danial; Bayan Toutounji; Tayf Toutounji (Case Reports in Surgery)
Intussusception is the invagination of a segment of the bowel into an adjacent segment. Here, we describe a middle-eastern case of an 11-year-old boy who presented to our institution with an intussusception caused by lymphoma but with nonspecific symptoms such as acute abdominal pain and a history of weight loss. His abdominal ultrasound and computed tomography (CT) showed ileocolic intussusception with a mass leading it. We resected the mass with the affected bowel and related lymph nodes, and the histological examination showed features of diffuse large B-cell Non-Hodgkin’s lymphoma (an uncommon histologic type in the Middle East). Known as intussusception, this urgent condition could distress infants and young children. However, in older children, the presentation is subtler. So, a lead point should be observed and the chance of malignancy should be kept in mind.